SYMPTOMS AND DETECTION OF THYROID CANCER (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Thyroid cancer is a growth of cells that begins in the thyroid gland. The thyroid gland is a butterfly-shaped gland located in the lower neck, just below the Adam's apple. The thyroid gland produces hormones that regulate heart rate, blood pressure, body temperature, and weight. Thyroid cancer may not cause any symptoms at first. But as it grows, it can cause signs and symptoms such as a lump in your neck, a change in your voice, and difficulty swallowing.